Evaluation of the time-dependent effect of an enzymatic denture cleanser tablet against six microbial species - Hayran, Yeliz; Aydin, Ali (Annals of Medical Research, 2021)
Aim: In elderly individuals, infection control is, essential, especially in the presence of severe bacteria such as oral environment. Prevention of biofilm formation in removable dental prosthesis, which is often used in elderly patients might help infection control. This study aimed to evaluate the time-dependent effect of an enzymatic tablet on six microorganisms cultured in two different denture base resins.Material and Methods: Polymethylmethacrylate (PMMA) and polyamide-resin were used in this study. 480 samples were prepared for each resin, and denture cleanser tablet was tested against C.albicans, S.mutans, S.gordonii, A.actinomycetemcomitans, S.aureus, and E.coli for 3rd, 5th, 10th, 20th, 40th, 80th, 160th, and 200th minutes. Cell viability (CV) was evaluated by MTT. ANOVA was used for statistics. Results: C.albicans exhibited higher CV in polyamide-resin compared to PMMA-resin in all tested durations. S.gordonii and A.actinomycetemcomitans exhibited higher CV in PMMA-resin except for 80th minute-S.gordonii, which had similar values. S.mutans had a higher CV in PMMA-resin than polyamide-resin at 3rd, 5th, 10th, 160th, and 200th minutes, and other values were similar to polyamide-resin. The tested concentration killed more than 75% of microorganisms except for 3rd and 5th minute-C.albicans on resins. S.aureus and E.coli had similar. CV of microorganisms on PMMA-resin was higher than on polyamide-resin. All microorganisms exhibited different adherence on the resins.Conclusions: Tablet cleanser was effective in all microorganisms and durations and over 10-minute durations provided over 76% cell death. Patients with a compromised immune system can safely use restorations composed of polyamide-resin or PMMA-resin with 40 min-treatment of tablet cleanser.Keywords: Bacteria; candida albicans; cell survival; denture bases; denture cleansers.
Keywords: Bacteria; candida albicans; cell survival; denture bases; denture cleansers.